Mathematical Communication Ability in SAVI Learning Model with Mathematics Board Game in terms of Mathematical Resilience - Ainurrachmani, Fitrania; Junaedi, Iwan; Dewi, Nuriana Rachmani (Unnes Journal of Mathematics Education, 2025)
This study aims to examine the quality of SAVI learning model implementation with a board game on mathematical communication skills, analyze the effect of mathematical resilience on mathematical communication skills, and describe mathematical communication skills in terms of mathematical resilience. This study used a mixed method of sequential explanatory type. The population of this research was all seventh-grade students of SMPIT Nidaul Hikmah Salatiga. The results showed that the implementation of the SAVI learning model with a quality math board game improved mathematical communication skills. Students' mathematical resilience has a positive effect on their mathematical communication skills. Students with high mathematical resilience fulfill all indicators of mathematical communication. Medium resilience students met indicators 2 and 3, needed guidance for indicators 1 and 4, and had not yet met indicator 5. Low-resilience students are only able to achieve indicators 1 and 4 with guidance. A special case, a student with high resilience and a habitual background of studying for Olympiads, showed significant differences between verbal and written mathematical communication.